Voided Ge/Si Platform to Integrate III-V Materials on Si. (22nd October 2019) - Bioud, Youcef Ataellah; Boucherif, Abderraouf; Myronov, Maksym; Patriarche, Gilles; Drouin, Dominique; Arès, Richard
Abstract : High-quality germanium epilayers on Si with low threading-dislocation densities were achieved by self-assembling nanovoids inside the Ge layer. This consists on the formation of porous Ge nanostructures by dislocation-selective electro-chemical etching followed by high-temperature treatment to transform it into quasi-monocrystalline voided Ge layer, which intercept dislocations and prevent them from reaching the upper layer.